New York, le désespoir du peintre dans The American Scene - Marie-Odile Salati (Anglophonia)
The modern city of New York, visited after a twenty-year absence, did not only come as a sentimental and cultural shock to the Europeanized novelist; it simply shattered his long-standing literary credos. The chaotic welter of impressions, as well as the substitution of uniform expressionless skyscrapers for the picturesque vestiges of the past under the pressure of the economic law, make the megalopolis an eminently non pictorial object and the task of the painter of life an impossible one. Since artistic composition is ruled out, the writer undertakes to capture epiphanic moments of acute perception, when a pattern of meaning suddenly looms out of the prevailing confusion, revealing the essence of the city. In order to convey the overriding impression of intense life going on, he adapts his technique to the object under observation, availing himself of all the resources provided by the materiality of language and by the capacity for compression afforded by metaphor, thus transmuting discordance into art.